Systemic traumatic stress: The couple adaptation to traumatic stress model - Goff, Briana S. Nelson (My University, 2008)
Research traditionally has focused on the development of symptoms in those who experienced trauma directly but overlooked the impact of trauma on the families of victims. In recent years, researchers and clinicians have begun to examine how individual exposure to traumatic stress affects the spouses/partners, children, and professional helpers of trauma survivors. However, empirically supported, theory-based literature that identifies the mechanisms by which interpersonal or "secondary trauma" occurs in response to traumatic events is limited. Here, we present the Couple Adaptation to Traumatic Stress Model, a systemic model of the development of interpersonal symptoms in the couple dyad based on empirical literature. Potential mechanisms and clinical vignettes are included to describe the systemic processes that occur with trauma couples. Areas for future research and clinical implications also are identified.
Keywords: Traumatic stress; Trauma exposure; Couples; Intimate relationships; Secondary trauma; Systemic traumatic stress